(untitled)
Metaphors can be regarded as systemic interrelations of multiple experiences which map one relatively stable domain to another. A number of cognitive linguists, such as KOvecses (2005) and Lakoff (2006), suggest that much metaphorical thinking arises from recurring patterns of physical experiences and sensori-motor interactions with the physical world. Gibbs (1999, p. 152) furthermore states that "people clearly a/so learn conceptual metaphors from their experiences with language." Research findings indicate that the default interpretations by First Language speakers were octuol/y the idiomCltic understandings, not the literal ones. The question could be asked whether this would be the case with Second Language speakers when drawing inferences from metaphorical expressions used by first language speakers, and specifically in the case of novel/creative metaphorical expressions.I assumed that this process might pose difficulties for ESl readers from an African environment when reading a business article in English which contained a fair amount of metaphorical expressions. I looked at both conventional metaphors and novel(creative metaphors. These were the metaphors with a source domain that presupposed meta-knowledge of the British English cultural environment. I also included in the research instrument a few orientational metaphors that were used in the business artcle. The findings of this study indicate concurrence with Gibbs (1999, cited in Yu zoog) that "c]ultura/ models ’in shaping what people believe, how they act, and how they speak about the world and their own experiences’ set up specific perspectives from which aspects of ’embodied experiences are viewed as particularly salient and meaningful in people’s lives. ... In short, ’social and cultural constructions of experience fundamentaJ/y shape embodied metaphor."’, journal=Journal for Studies in Humanities and Social Sciences, year=2014, month=Feb., pages=093–108